CAUSES AND CONSEQUENCES OF EXCHANGE RATE DYNAMICS IN UKRAINE - E. Tkach; S. Tkach (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
This article investigates factors that influence the exchange rate formation process in Ukraine, as well as the exchange rate fluctuations effects on the economy of our country. The inappropriate use of exchange rate hard peg in terms of permanently high inflation level is proved. The measures needed to balance the monetary and exchange relations and to prevent sharp fluctuations in the foreign exchange market in Ukraine are proposed.